Horyzontalna pomoc publiczna w latach 2001-2005 w odniesieniu do wyłączeń grupowych - Kras, Andrzej (Horizontal State Aid in the Light of the EU Council Regulation no 994/98 - Aims and Results of theirs Application Between 2001 and 2005, 2008)
The purpose of this article is to describe the horizontal state aid in the light of EU Council Regulation no 994/98. This legal act gave the competence to the EU Commission to decide, which categories of the horizontal state aid can be acknowledged as compatible with the EU common market and not a subject of the notification. In years 2001-2005 on the basis of the Council Regulation the EU Commission has adopted five block exemption regulations, which were aimed at tackling problems which may arise in any industry and region and on simplification of the state aid procedure. Regulations concerned: training aid, employment aid, small and medium enterprises aid, agriculture aid and fishery aid. Every 5 years Commission is obliged to submit a special report of the practical function of the Council's Regulation. Last results showed that the Council and subsequent Commission's regulations had a positive impact on the sphere of EU competition and main purposes were achieved. Simultaneously main problems in utilization of provisions of the regulations had been found and that will be the subject of the further work of the EU Commission.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 328-343